Immune checkpoint blockers and ovarian cancer - Chinmoy K Bose (Indian Journal of Medical and Paediatric Oncology)
Although the idea, called “cancer immunotherapy,” is very appealing and has previously been shown to work in several mouse models of cancer, it has in general been very difficult to translate cancer immunotherapy approaches to humans. Because of this frustration, by the 1990s, many scientists and biotechnology companies had given up on the idea of cancer immunotherapy. After few years, first detection T-cell suppression of effect of cytotoxic T-lymphocyte antigen-4 (CTLA4) molecule was established. Antibody (Ab) to CTLA4 could increase T-cell starting a completely new age of tumor immunology. Immune checkpoints are new ways in manipulation of immunological control over malignant tumors. It has lent an important measure to manage, especially recurrent and refractory cancers and those cancer where there is an unmet need like recurrent melanoma, renal cell carcinoma, and recurrent ovarian cancer. As a new development, this subject is experiencing rapid progress, and multiple avenues are opening up. Although there are many hurdles to overcome this needs constant updating, especially for students of ovarian cancer who are looking at it with much hope.